2013
DOI: 10.1371/journal.pone.0069310
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Influences the S-Methadone Metabolite Plasma Concentration

Abstract: Background and ObjectivesHeroin-dependent patients typically contract hepatitis C virus (HCV) at a disproportionately high level due to needle exchange. The liver is the primary target organ of HCV infection and also the main organ responsible for drug metabolism. Methadone maintenance treatment (MMT) is a major treatment regimen for opioid dependence. HCV infection may affect methadone metabolism but this has rarely been studied. In our current study, we aimed to test the hypothesis that HCV may influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
2
18
1
Order By: Relevance
“…This study is limited since HCV status was only determined based upon antibody testing, which does not differentiate between active and resolved infections. Despite these limitations, both studies are in agreement that HCV influences plasma methadone concentration in OUD patients on methadone [67,68]. In contrast to the above-mentioned studies, we did not observe a significant effect of fibrosis stage on methadone metabolism.…”
Section: Ln([r]-eddp/methadone Concentration)supporting
confidence: 69%
See 1 more Smart Citation
“…This study is limited since HCV status was only determined based upon antibody testing, which does not differentiate between active and resolved infections. Despite these limitations, both studies are in agreement that HCV influences plasma methadone concentration in OUD patients on methadone [67,68]. In contrast to the above-mentioned studies, we did not observe a significant effect of fibrosis stage on methadone metabolism.…”
Section: Ln([r]-eddp/methadone Concentration)supporting
confidence: 69%
“…However, this investigation has several weaknesses including lack of clarity as to how HCV status was defined and determined, measurements limited to peak methadone concentration, a homogeneous participant population consisting of males of limited racial and ethnic diversity, and absence of cirrhotic participants [67]. In a Taiwanese population, Wu et al [68] found that total plasma methadone and (R)-methadone concentrations were significantly higher in HCV seropositive compared with HCV seronegative participants. This study is limited since HCV status was only determined based upon antibody testing, which does not differentiate between active and resolved infections.…”
Section: Ln([r]-eddp/methadone Concentration)mentioning
confidence: 99%
“…In our previous studies, the SNPs on CYP2B6 were significantly associated with plasma S -methadone concentration, the ratio of S -methadone/methadone dose, and the S -methadone clearance [6]. We also found that the CYP2B6 has a higher level of activity in the HCV-positive patients [20]. SNPs in CYP3A4 were significantly associated with COWS, TESS, and betel nut use [12].…”
Section: Resultsmentioning
confidence: 92%
“…A higher initial methadone dose (P = 0.038), higher plasma concentrations of (R,S)-methadone (P = 0.038) and R-methadone (P = 0.028), lower ratio of S-EDDP/methadone dose (P = 0.043), higher levels of AST (P = 0.048) and ALT (P = 0.046), and a longer addiction duration (P b 0.0001) were found in the HIV(+)/HCV(+) or HCV(+) patients than the HIV(−)/HCV(−) patients ( Table 1). The results of urine morphine test, which was used as a surrogate indicator for the effectiveness of opioid dependence treatment [6], were not statistically different among subjects grouped by their status of HIV and/or HCV infection.…”
Section: To the Editormentioning
confidence: 86%